2022
DOI: 10.1002/pmh.1558
|View full text |Cite
|
Sign up to set email alerts
|

Systems Training for Emotional Predictability and Problem Solving for borderline personality disorder: A systematic review

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…To achieve emotional stability, patients learn basic emotion and behaviour management skills (Blum et al, 2002). A recent systematic review of the current studies concluded that STEPPS seems to be an effective treatment for patients with BPD (Ekiz et al, 2022). To date, no studies have been conducted into the effects of STEPPS in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve emotional stability, patients learn basic emotion and behaviour management skills (Blum et al, 2002). A recent systematic review of the current studies concluded that STEPPS seems to be an effective treatment for patients with BPD (Ekiz et al, 2022). To date, no studies have been conducted into the effects of STEPPS in older adults.…”
Section: Introductionmentioning
confidence: 99%